EFFECT OF ETHANOLIC EXTRACT OF Annona muricata L SEEDS POWDER TO DECREASE BLOOD GLUCOSE LEVEL OF WISTAR MALE RATS WITH GLUCOSE PRELOAD - Rian Ulva Rizki Hasanah; Elza Sundhani; Nunuk Aries Nurulita (UPT Penerbitan Universitas Jember)
Based on data from World Health Organization(WHO) diabetes mellitus was the direct cause of death of1.5 million people, more than 80% of deaths due todiabetes occurs in middle-income countries and low(WHO, 2014). According to the Basic Health Research(Riskesdas) in 2013, the incidence of diabetes mellitus inIndonesia increased by two times greater than in 2007.Annona muricata L is used as a traditionalmedicine to lower blood glucose levels with containtannin, phytosterols, calcium oxalate, alkaloids murisin(Arief and Hariana, 2006), flavonoids and essential oils(Surbakti, 1994). Flavonoid compounds have animportant role in the prevention of diabetes and itscomplications (Jack, 2012). Previous research showedthat bark of plants soursop has a most excellent efficacycompared with the roots and leaves of the Annonamuricata L in lowering blood glucose levels in male ratsinduced streptozozin (Rahmawati, 2014).This study aimed to examine the effect ofethanolic extract of Annona muricata L. seeds powder ondecreasing blood glucose level in wistar strain male ratwith glucose loading.